Cutaneous Manifestations of Sarcoidosis : Reports of Two Cases - Akter, Tahmina; Zahid, Reza Bin (BIRDEM Medical Journal, 2017)
Sarcoidosis is a multisystem disease that may involve any organ or system. Cutaneous manifestations occur in 25- 30% of patients with sarcoidosis. Sarcoidosis can present with reactive non- specific lesions like erythema nodosum or specific manifestations showing granulomatous microscopic pathology including papules, plaques, lupus pernio, scar sarcoidosis, and rare morphologies such as alopecia, hypopigmented patches and ichthyosiform lesions. Here we present two interesting cases who presented with cutaneous manifestations and causing diagnostic diemma. Birdem Med J 2016; 6(2): 130-133